1976
DOI: 10.1002/bbpc.19760800502
|View full text |Cite
|
Sign up to set email alerts
|

Motion of Guest Molecules in Clathrates

Abstract: First the term clathrates is explained and illustrated more precisely on the three examples Ice Clathrate, Urea Clathrate, and Quinol Clathrate. Then a review of experimental results, which exist in the literature in the following domains, is given: Thermodynamic studies, dielectric relaxation, far infrared, infrared, and Raman spectroscopic studies, nuclear magnetic and nuclear quadrupole resonance, electron paramagnetic resonance, magnetic susceptibility, and neutron scattering. Emphasis is laid on the infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 93 publications
(24 reference statements)
3
22
0
Order By: Relevance
“…Our complementary X-ray diffraction experiments show that the low-T phase of the x = 0.97 sample is not R3 ferroelectric, as stated previously [11], but rather antiferroelectric triclinic without a global threefold symmetry and accordingly with three orientation states. The structure basically consists of ferroelectric chains running along c which are arranged in sheets of alternating sign, as evidenced by superlattice reflections and presumed previously [13]. The dielectric data of all samples show primary relaxations in ε c at temperatures comparable to the transition temperatures of the ordering samples and secondary relaxations in ε a at lower T around 20 K. ε c is significantly larger than ε a , indicating that it is mainly the c-component of µ, µ c , which is involved in the primary relaxations and the ordering process, whereas the perpendicular component is involved in the secondary relaxations.…”
supporting
confidence: 58%
“…Our complementary X-ray diffraction experiments show that the low-T phase of the x = 0.97 sample is not R3 ferroelectric, as stated previously [11], but rather antiferroelectric triclinic without a global threefold symmetry and accordingly with three orientation states. The structure basically consists of ferroelectric chains running along c which are arranged in sheets of alternating sign, as evidenced by superlattice reflections and presumed previously [13]. The dielectric data of all samples show primary relaxations in ε c at temperatures comparable to the transition temperatures of the ordering samples and secondary relaxations in ε a at lower T around 20 K. ε c is significantly larger than ε a , indicating that it is mainly the c-component of µ, µ c , which is involved in the primary relaxations and the ordering process, whereas the perpendicular component is involved in the secondary relaxations.…”
supporting
confidence: 58%
“…The structure of the dipole system in the dielectrically ordered phase in methanol-␤-hydroquinone clathrate, as determined from the analysis of the superlattice reflections below T c , agrees well with the ground state calculated by Monte Carlo simulations 9 and lattice sum calculations. The temperature behavior of the correlation length c and Ќ is well described by the corresponding quasi-1D model by Scalapino et al 7 The structural investigations therefore confirm the microscopic picture of low-dimensional ordering and fluctuations of the methanol pseudospins in the ␤-hydroquinone cagework, as it was suggested by the dielectric experiments.…”
Section: Discussionsupporting
confidence: 69%
“…The 4:2 pattern fills the hexagonal basal plane in a regular fashion: Every dipole has the same environment of ferro-and antiferroelectrically oriented pseudospins. This 2-k 1 ground state is also obtained from Monte Carlo calculations 9 and simple lattice sum calculations, considering the EDD interaction of the guest molecules, only (see Ref. [10] for the case of acetonitrile).…”
Section: Ordered Phasementioning
confidence: 97%
“…23 Other diffraction experiments have shown that the cell parameters and atomic positions of the ␤-hydroquinone framework change little upon inclusion of small guest molecules. 24,7,12 In the following, we will use the empty (Q ␤ ) 3 •HCl host framework as an experimental reference structure.…”
Section: B Crystal Structures and Geometry Optimizationsmentioning
confidence: 99%
“…No ab initio calculations for any clathrate crystals appear to exist in the literature up until now. A number of computational studies of the ␤-hydroquinone clathrates using empirical force fields have been published, [7][8][9][10][11][12] however, as well as many experimental studies based on diffraction, calorimetry, ESR, NQR, Mössbauer, and far-IR techniques ͑see Refs. 6, 13-15, and references therein͒.…”
mentioning
confidence: 99%